PENGARUH MODEL PROBLEM BASSED LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS ULASAN FILM SISWA KELAS XI SMA N 7 PADANG - Sukardi, Icha Putri; R.,, Syahrul (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTÂ This study has three objectives which are described as follows: (1) Describe the ability to write a film review text in class XI SMA N 7 Padang before using the Problem Based Learning model assisted by audiovisual media. (2) Explaining the skills of writing a movie review text for grade XI of SMA N 7 Padang after using the Problem Based Learning model assisted by audiovisual media. (3) Explain the influence of the Problem Based Learning model assisted by audiovisual media on the skills of writing film review texts on grade XI students of SMA N 7 Padang. This type of research is quantitative research with experimental methods. The design of this research is one group pretest and posttest design. The population in this study were class XI students of SMA N 7 Padang, who were registered in the 2018/2019 school year as many as 332 people. The sample in this study was 33 students who were determined using a technique (purposive sampling). The variable of this study is the text writing skills of film reviews before and after using the Problem Based Learning learning model assisted by audiovisual media of class XI students of SMA N 7 Padang.Â Kata kunci: Pengaruh, model problem bassed learning berbantuan media audiovisual, menulis teks ulasan filmÂ